Leksyka słowiańskich dialektów miejskich: egzoetnonimy w gwarze Warszawy, Brna i Moskwy - Juszczak, Bartosz (Studia Rossica Posnaniensia, 2020)
The present study concentrates on the issue of exoethnonyms and, in particular, exoethnonyms replacing orthonyms in the vocabulary of Slavonic urban dialects – namely, the urban dialect of Warsaw, the Hantec slang of Brno and the urban dialect of Moscow. Based on the data extracted from dictionaries, it was possible to select such designations. From the linguistic point of view, these nominations are either occasionalisms or names more deeply rooted in the lexical system of the urban dialects in question. The article includes the analysis and classification of the research data in terms of the linguistic and extralinguistic motivation and axiological evaluation of particular items.